Survival after secondary liver resection in metastatic colorectal cancer: Comparing data of three prospective randomized European trials (LICC, CELIM, FIRE‐3). Issue 8 (4th December 2021) - Moehler, Markus; Folprecht, Gunnar; Heinemann, Volker; Holch, Julian Walter; Maderer, Annett; Kasper, Stefan; Hegewisch‐Becker, Susanna; Schröder, Jan; Overkamp, Friedrich; Kullmann, Frank; Bechstein, Wolf Otto; Vöhringer, Matthias; et al.
Abstract: Metastatic colorectal cancer (mCRC) patients with liver‐limited disease (LLD) have a chance of long‐term survival and potential cure after hepatic metastasectomy. However, the appropriate postoperative treatment strategy is still controversial. The CELIM and FIRE‐3 studies demonstrated that secondary hepatic resection significantly improved overall survival (OS). The objective of this analysis was to compare these favorable outcome data with recent results from the LICC trial investigating the antigen‐specific cancer vaccine tecemotide (L‐BLP25) as adjuvant therapy in mCRC patients with LLD after R0/R1 resection. Data from mCRC patients with LLD and secondary hepatic resection from each study were analyzed for efficacy outcomes based on patient characteristics, treatment and surveillance after surgery. In LICC, 40/121 (33%) patients, in CELIM 36/111 (32%) and in FIRE‐3‐LLD 29/133 (22%) patients were secondarily resected, respectively. Of those, 31 (77.5%) patients in LICC and all patients in CELIM were R0 resected. Median disease‐free survival after resection was 8.9 months in LICC, 9.9 months in CELIM. Median OS in secondarily resected patients was 66.1 months in LICC, 53.9 months in CELIM and 56.2 months in FIRE‐3‐LLD. Median age was about 5 years less in LICC compared to CELIM and FIRE‐3. Secondarily resected patients of LICC, CELIM and FIRE‐3 showed an impressive median survival with a tendency for improved survival for patients in the LICC trial. A younger patient cohort but also more selective surgery, improved resection techniques, deep responses and a close surveillance program after surgery in the LICC trial may have had a positive impact on survival. Abstract : What's new? The management of liver‐limited disease (LLD) in patients with metastatic colorectal cancer (mCRC) is controversial, the optimal treatment has not been defined. Here, data from mCRC patients with LLD and secondary hepatic resection from the prospective randomized trials CELIM, FIRE‐3 and LICC were compared. Secondarily resected patients from these trials showed an impressive overall survival (OS), with a tendency for improved OS in LICC. Reasons might be the deep response induced by chemotherapy and surgery combined with close surveillance after surgery. Further prospective, randomized clinical trials are strongly needed to clarify these benefits.